Cost-Effectiveness Analysis of a Three-Drug Regimen Containing Bevacizumab for the Treatment of Recurrent Pediatric Medulloblastoma in China: Based on a COG Randomized Phase II Screening Trial - Zhaoyan Chen; Fangyuan Tian; Xi Chen (Frontiers Media S.A., 2022)
BackgroundMedulloblastoma is the most common malignant brain tumor of childhood, accounting for 6 to 7 percent of all childhood CNS tumors. The purpose of this study was to evaluate the economic efficacy of a bevacizumab combined with temozolomide + irinotecan regimen for the treatment of recurrent pediatric medulloblastoma in China.MethodsThe data analyzed were from a randomized phase II screening trial that showed an improved survival benefit in child patients with recurrent medulloblastoma treated with a T+I+B combination regimen. A Markov model is constructed to estimate the incremental cost-effectiveness ratio (ICER) from the perspective of Chinese society. The uncertainty in the model is solved by one-way certainty and probabilistic sensitivity analysis.ResultsOur base case analysis showed that the total costs of treatment increased from $8,786.403 to $27,603.420 with the combination bevacizumab vs. the two-agent chemotherapy regimen. Treatment with T+I+B combination therapy was associated with an increase in effectiveness of 0.280 QALYs from 0.867 to 1.147 QALYs T+I regimen. The incremental cost-effectiveness ratio was $67,203.632/QALY, which exceeded our pre-specified willingness-to-pay threshold ($38,136.26/QALY). Cost changes associated with grade 3-4 AE management, tests used, or hospitalization costs had little effect on the ICER values predicted by sensitivity analysis.ConclusionsTaken together, the results of this study suggest that the combination of bevacizumab with temozolomide and irinotecan is not a cost-effective option from the perspective of Chinese payers as a first-line treatment option for children with recurrent medulloblastoma in China.